2009
DOI: 10.1007/s11845-009-0277-9
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis presenting with severe hypocalcaemia

Abstract: Disorders of calcium metabolism, especially hypercalcemia and hypercalceuria, are common in sarcoidosis. They are caused by extra renal unsuppressed production of 1,25 dihydroxy vitamin D at the level of the sarcoid granuloma. Hormonal changes during pregnancy have a physiological synergistic effect on this mechanism, which is primarily parathyroid hormone (PTH) dependant. However, the combination of primary hypoparathyroidism with hypocalcemia and sarcoidosis is rare. Di George syndrome, is a dysmorphic disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…19 In addition, the most recent large population-based studies have not confirmed an increased incidence of lymphoma in patients with sarcoidosis. 20 Finally, clinically it is not likely that this patient has sarcoidosis, given that there have been only several reports of sarcoidosis or possible sarcoidosis in patients with DiGeorge syndrome (1 with mediastinal adenopathy, 21 1 with “sarcoid dermatitis” after isoniazid therapy with a negative “sarcoidosis workup,” 22 and 1 “suggestive of ocular sarcoidosis” 23 ).…”
Section: Discussionmentioning
confidence: 94%
“…19 In addition, the most recent large population-based studies have not confirmed an increased incidence of lymphoma in patients with sarcoidosis. 20 Finally, clinically it is not likely that this patient has sarcoidosis, given that there have been only several reports of sarcoidosis or possible sarcoidosis in patients with DiGeorge syndrome (1 with mediastinal adenopathy, 21 1 with “sarcoid dermatitis” after isoniazid therapy with a negative “sarcoidosis workup,” 22 and 1 “suggestive of ocular sarcoidosis” 23 ).…”
Section: Discussionmentioning
confidence: 94%
“…Destruction of the parathyroid glands secondary to granulomatous infiltration (e.g. sarcoidosis, amyloidosis, Riedel’s thyroiditis) has been reported (30, 31, 32, 33, 34).…”
Section: Nonsurgical Causes Of Hypoparathyroidismmentioning
confidence: 99%
“…В редких случаях причиной гипопаратиреоза могут стать инфильтративные заболевания, такие как саркоидоз, амилоидоз, тиреоидит Риделя и метастатическое поражение ОЩЖ [12][13][14][15]. Ткань ОЩЖ относительно не восприимчива к лучевому повреждению, тем не менее в литературе описаны очень редкие случаи радиационно-индуцированного гипопаратиреоза [16][17][18][19].…”
Section: этиологияunclassified